Buffalo Dance : The Journey of York - Walker, Frank X., 1961- (Book collections on Project MUSE., 2022)
When Frank X Walker's compelling collection of personal poems was first released in 2004, it told the story of the infamous Lewis and Clark expedition from the point of view of York, who was enslaved to Clark and became the first African American man to traverse the continent. The fictionalized poems in Buffalo Dance form a narrative of York's inner journey before, during, and after the expedition--a journey from slavery to freedom, from the plantation to the great Northwest, from servant to soul yearning to be free. In this expanded edition, Walker utilizes extensive historical research, interviews, transcribed oral histories from the Nez Perce Reservation, art, and empathy to breathe new life into an important but overlooked historical figure. Featuring a new historical essay, preface, and sixteen additional poems, this powerful work speaks to such themes as racism, the power of literacy, the inhumanity of slavery, and the crimes against Native Americans, while reawakening and reclaiming the lost "voice" of York.